Investigating the Effects of Shockwave and Percussion Massage Gun on Subacute Myofascial Pain in Gasterocenemious Muscle - Seyedeh Zohreh Hosseini; Siamak Bashaardost Tajali; Khadijeh Otadi; Kazem Malmir; Alireza Hosseinzadeh Chaijan (Journal of Modern Rehabilitation)
Introduction: Myofascial pain syndrome is a common musculoskeletal injury, especially among athletes, typically treated with symptomatic invasive and non-invasive methods. This study compares the effects of massage guns and radial extracorporeal shock wave therapies on myofascial pain syndrome symptoms in amateur athletes. Materials and Methods: In this clinical trial, 45 amateur athletes (18-30 years old) were recruited, who were randomly assigned to 15-member groups of shock wave, massage gun, and control (routine treatment included electrotherapy and stretching, which was applied on three groups). After initial evaluations of the pain intensity, pain pressure threshold (PPT), isometric muscle strength, and range of motion (ROM), the patients received single-session treatment and were immediately reassessed. Results: The results showed pain relief and improved PPT following shock wave plus routine treatment (P=0.03). The control group had less pain, while pain intensity and PPT did not change. The variables were not significantly different between the groups (P=0.12). Shock wave along with routine treatment increased plantar flexion ROM (P=0.00), unlike the massage gun. Additionally, dorsiflexion ROM (P=0.63) and maximal isometric gastrocnemius muscle strength (P=0.95) remained unchanged in all groups. Conclusion: One session of massage gun therapy immediately reduced gastrocnemius muscle pain, while it failed to change PPT, maximal isometric gastrocnemius muscle strength, or dorsiflexion and plantar flexion ROM. However, shock wave therapy immediately increased plantar flexion ROM and PPT, and reduced pain intensity. These modalities led to limited changes, suggesting the need for repeated sessions and supplementary treatments.